Older Patients Are Less Affected by Radiochemotherapeutic Treatment than Younger - Welling, Max J.; Losensky, Wencke; Wächter, Katharina; Schilling, Teresa; Frank, Friedrich; Haas, Matthias; Fietkau, Rainer; Distel, Luitpold; Weiß, Stephanie (BioMed Research International, 2018)
Purpose: The general assumption is that cancer therapy impairs the quality of life in elderly patients more than in younger ones. We were interested in the effects of radiochemotherapeutic treatment on the quality of life of elderly patients compared to younger patients and compared to normative data of a general German population. Methods and Materials: A total of 465 patients completed the EORTC QLQ-C30 questionnaire. Repetitive completion of the questionnaire over time led to 1407 datasets. Our patient cohort contained 197 (42.4%) patients with colorectal cancer followed by 109 (23.4%) patients with head and neck cancer, 43 (9.2%) patients with lung cancer, and 116 (25%) with other types of cancer. Patients were categorized into five age groups, the respective cut-offs being 40, 50, 60, and 70 years. Normative data were drawn from a population study of a general German population. Results: Functional scores and symptom scores were approximately stable between the different age groups. Our data does not suggest a significant difference between the investigated age groups. Advancing age evened out the differences between the normative data of the general German population and the cancer patients in 11 of 15 scores. Conclusions: The general belief about younger patients having fewer physical and psychological problems related to radiochemotherapy needs to be reconsidered. Overall resilience of older patients is apparently underestimated.
EVALuna2:36461